2019
DOI: 10.1155/2019/4315032
|View full text |Cite
|
Sign up to set email alerts
|

Colon Cancer Sidedness, Presentation, and Survival at Different Stages

Abstract: Background. Several prognostic factors have been used to guide therapy for colon cancer (CC). However, the relationship between CC laterality (sidedness) and prognosis remains under investigation. Objectives. To assess the effect of laterality on CC presentation and survival, using a Surveillance, Epidemiology, and End Results (SEER) population-based cohort. Methods. A retrospective cohort study using data from the SEER program (2007-2015). Results. Of the 163,980 patients with CC, 85,779 (52.3%) presented wit… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
48
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
9

Relationship

2
7

Authors

Journals

citations
Cited by 54 publications
(55 citation statements)
references
References 37 publications
7
48
0
Order By: Relevance
“…It was observed that patients with right-sided tumors presented a significantly decreased OS compared to left-sided tumors. This phenomenon has also been described previously [39][40][41][42]. Baran B et al reported that treatment response differed among the left and right-sided tumors.…”
Section: Discussionsupporting
confidence: 81%
See 1 more Smart Citation
“…It was observed that patients with right-sided tumors presented a significantly decreased OS compared to left-sided tumors. This phenomenon has also been described previously [39][40][41][42]. Baran B et al reported that treatment response differed among the left and right-sided tumors.…”
Section: Discussionsupporting
confidence: 81%
“…Finally, Ulanja MB et al, in a retrospective analysis of 163,980 patients with colon cancer, concluded that tumor sidedness might affect presentation and survival rates at different stages of the disease. They reported that patients with left-sided tumors presented better overall survival rates in stages I, III/IV; whereas, patients with right-sided tumors presented better survival rates only in stage II disease [42]. The results from our study and the studies mentioned above could be explained by the findings of Dejea CM et al The authors examined 36 tissues from the right (15 CRC and 4 adenomas) and left-sided tumors (15 CRC and 2 adenomas) and demonstrated the association of bacterial aggregates (biofilms) in the colon with CRC.…”
Section: Discussionmentioning
confidence: 99%
“…As for stage at diagnosis, our study demonstrated that most right-sided cases were stage III while left-sided cases were stage IV and these results were in agreement with the results of the study by Paul J Ross et al [24]. Conversely, these results did not agree with the study by Mark B. Ulanja et al which reported that right-sided colon cancer was more significantly associated with a more advanced stage when compared to left-sided colon cancer [25]. This can be due to the more advanced tumor (T) and lymph node (N) stages in right colon cancer versus the more potential for metastases (M stage) in left colon cancer in our study group.…”
Section: Discussionsupporting
confidence: 70%
“…Tumor genetic and anthropomorphic features, as well as survival estimates, varies depending on right-or left-sided tumor localization. Compared to left-sided colon cancer, rightsided colon cancer is associated with female sex, older age and a higher proportion of mutations in the KRAS and BRAF oncogenes, and left-sided colon cancer generally has worse prognosis [33,34]. Furthermore, in some cohorts, e.g.…”
Section: Introductionmentioning
confidence: 99%